Challenges in the dermocosmetic market and its strategic implications : Aligning Teint Ideal’s brand strategy to improve performance - Heil, Verena (2016)
This paper analyses the difference in sales performance of two make-up sub-brands in relation to consumer perceptions and attitudes. While one of the make-up brands is performing well, the other brand is continuously decreasing in sales. The thesis investigates the strategic implications which consumer behavior and attitude have on brand performance. Primary as well as secondary research are conducted to understand the situation and postulate a strategy for the brand which is performing poorly. Findings reveal that the difference in perception of the two sub-brands plays a pivotal role in consumer decisions. The positioning of the poorly performing sub-brand needs to focus on correcting perceived short-falls in effectiveness, versus the expectations of consumers in the pharma channel. The challenge will be to define a strategy without losing the DNA of the parent brand yet still maintaining a differentiated position from competing brands in the same portfolio and category. It is a deluxe brand management and portfolio management problem case where all the key factors of brand management come together. This issue confirms the relevance of effective portfolio management, coherent branding, and strategic positioning all within the context of brand architecture.